Description of student learning difficulties in the thermochemistry - Silvira Rahmi; Fajriah Azra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Thermochemistry is a material high school students study in class XI MIPA in odd semesters. In this material, 83.69% of SMAN 13 Padang class XI MIPA students still need to achieve the minimum completeness criteria set. It indicates that students have learning difficulties. Learning difficulties are failures to attain learning goals characterized by low learning outcomes. This study aims to determine the percentage of students who experience learning difficulties for each indicator on thermochemistry material and determine the factors that cause learning difficulties experienced by students in terms of learning methods. This research is a type of descriptive research. The sample for this research was students in class XI MIPA 6 at SMAN 13 Padang in the 2022/2023 academic year, which consisted of 34 people. The research instrument was a diagnostic test with four-tier multiple-choice questionnaires and interviews. The data analysis used is descriptive, namely analyzing and providing an understanding of the data in the form of numbers so that an overview can be given in an orderly, concise, and transparent manner. The results of this study stated that students of SMAN 13 Padang had difficulty learning thermochemistry material in the high category. The highest difficulty level is found in the sixth indicator (determining the ∆H value of the reaction through a calorimeter experiment), which is 90.20%. Meanwhile, the lowest level of learning difficulty for students is found in the first indicator (explaining differences in systems and environments in chemical reactions), which equals 42.16%. Learning difficulties experienced by students are caused by ineffective learning methods, such as not making a study schedule and not carrying it out, not reading and not taking notes, not repeating material, not concentrating, and not doing assignments.